Adverse events following immunization with oral poliovirus in Kinshasa, Democratic Republic of Congo: preliminary results - Nzolo, Didier (Maney Publishing, 2013)
AIM: We investigated the nature and frequency of adverse events following immunization (AEFI) associated with oral polio vaccines (OPV) in the general population in Kinshasa, Democratic Republic of Congo (DR Congo). METHODS: The DR Congo National Pharmacovigilance Centre organized active AEFI surveillance during mass immunization campaigns for the general population from March to June 2011. A patient individual case safety report was used as a questionnaire and addressed to pupils and students from high schools and universities who had any adverse events after OPV administration. We used the preferred term from the WHO Adverse Reaction Terminology for AEFI designation. Here is presented the results of the second step of the mass immunization campaign. RESULTS: A total of 767 patients reported AEFI during the second step. Sex distribution shows that 512 (66.8%) students were females, while 255 (33.2%) were males, giving a female/male ratio 2∶1. The average age was 16.8±5.19 years (ranged: 6–35.5 years). Each person reported a mean of 1.33±0.6 AEFI. The average AEFI onset duration was 1.74±1.16 days post-vaccination, ranging from 1 to 9 days. Headache (22.4%), abdominal pain (17.2%), fever (11.7%), diarrhea (9.9%), and asthenia (7.5%) were the common symptoms. Paralysis and asthma-like reactions were rare and serious adverse events in this study. The most affected systems were gastro-intestinal (33.5%) and nervous system (29.3%). Rechallenge was positive for 173 persons (22.6%). CONCLUSION: OPV-related AEFIs are not uncommon, although it is under-reported. Active AEFI surveillance during mass immunization campaigns is very important and may help to detect rare and serious adverse events. Further investigation will be important to identify risk of AEFI with OPV in adults and is warranted to elucidate the cause of this association in the Congolese environment.